1987
DOI: 10.1111/j.1600-0765.1987.tb01539.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between histological and clinical parameters during human experimental gingivitis

Abstract: The purpose of this investigation was to study stereologically the histopathologic alterations occurring during a human experimental gingivitis, and to establish a relationship between clinical parameters and histologic findings. Eight dental students volunteered for the study. After a prophylaxis they performed optimal oral hygiene for 3‐4 weeks to reach mean plaque and gingival indices approaching zero. They then abandoned all oral hygiene procedures for a period of 21 days. At d 0, 4, 7, 14 and 21, Plaque I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
61
1
2

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(69 citation statements)
references
References 18 publications
4
61
1
2
Order By: Relevance
“…Brecx et al (1987) [63] performed an experimental gingivitis study in 8 dental students (a group identical to our young adults) and reported that plasma cells occupied only 1% of the lesions. Differences in the cellular composition of the gingival lesions were also detected by Page et al (1975) [64] in a study in young and old monkeys, and by [35] Berglundh and Lindhe (1993) who investigated developing gingivitis in young and old dogs.…”
Section: Discussionmentioning
confidence: 69%
“…Brecx et al (1987) [63] performed an experimental gingivitis study in 8 dental students (a group identical to our young adults) and reported that plasma cells occupied only 1% of the lesions. Differences in the cellular composition of the gingival lesions were also detected by Page et al (1975) [64] in a study in young and old monkeys, and by [35] Berglundh and Lindhe (1993) who investigated developing gingivitis in young and old dogs.…”
Section: Discussionmentioning
confidence: 69%
“…One could speculate that endothelial PNAd and ICAM-1 may be responsible for a sustained recruitment of memory B cells in clinically healthy gingiva. This memory B cell trafficking may take place along with the well-documented polymorphonuclear cell emigration, a well-recognized phenomenon in a clinically healthy sulcus (44,45). Such gingival memory B cells were obviously functional, as they were able to secrete IgG and IgA after in vitro polyclonal stimulation in the current study.…”
Section: Discussionmentioning
confidence: 71%
“…The additional finding of no significant change in the total macrophage population with the development of experimental gingivitis in humans was also noted by others. 12,13 There have been few reliable phenotypic markers for macrophages available until recently. This limitation has been addressed in part by the development of the high specificity monoclonal antibodies Ber-MAC3, 7 27E10, 8 25F9, 9 and RM3/1.…”
Section: Discussionmentioning
confidence: 99%